2013
DOI: 10.1021/jp311832d
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Imaging of Freezing Drops: Still No Preference for the Contact Line

Abstract: on liquid−solid nucleation arrived at conflicting results regarding a preferred status of the triple line between water, air, and an ice-catalyzing substrate. Temperature nonuniformity within drops and substratedependent contact angles have been suggested as culprits in a recent review by Sear (Int. Mater. Rev. 2012, 57, 328−356).To that end, we redesigned our earlier experiment to allow substrate-induced cooling and a side view with a second high-speed camera. The two camera views pinpoint the spatial locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 18 publications
7
52
1
Order By: Relevance
“…Gurganus et al (2011) tested 189 drops and found that there is no preference to form the ice germ at the 3-phase boundary (surfacedroplet-air) or 3-phase contact line over the 2-phase contact area. Gurganus et al (2013) confirmed their previous observations with an improved version of their experimental setup (i.e. a side view of the tested droplets was possible with a second high-speed camera).…”
Section: Three-phase Contactsupporting
confidence: 86%
See 1 more Smart Citation
“…Gurganus et al (2011) tested 189 drops and found that there is no preference to form the ice germ at the 3-phase boundary (surfacedroplet-air) or 3-phase contact line over the 2-phase contact area. Gurganus et al (2013) confirmed their previous observations with an improved version of their experimental setup (i.e. a side view of the tested droplets was possible with a second high-speed camera).…”
Section: Three-phase Contactsupporting
confidence: 86%
“…Recently, Gurganus et al (2011) and Gurganus et al (2013) reported experimental results which contradict the previously mentioned mechanisms. Using an improved and modified version of a cold stage (Suzuki et al, 2007) to avoid the point-like contact (i.e., the contact between the drop and the IN) and to minimize the temperature variation on the water drop surface, the preferred location to nucleate an ice crystal was investigated on silicon wafers.…”
Section: Three-phase Contactmentioning
confidence: 88%
“…There have been quite some debates about the initiation site of nucleation. Some authors [48][49][50] suggested that the nucleation preferentially starts at the three-phase contact line, while others 51,52 claimed that it starts randomly at the whole solid-liquid interface. The controversy might be caused by different test environment or Such a nucleation rate is plotted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Suzuki et al (2007) found from their experiments with water droplets on silicon surfaces coated with various silanes that the temperature at which nucleation occurs at a contact line depends on the contact angle between water and the substrate. On the other hand, Gurganus et al (2011Gurganus et al ( , 2013 investigated the freezing of droplets deposited on clean and coated silicon wafers and did not observe any preference of nucleation at the contact line. The same group also studied this phenomenon on catalyst substrates with imposed surface structures and found that the preferred nucleation site was the contact line in the case of nanoscale texture but not for microscale texture (Gurganus et al, 2014).…”
Section: Introductionmentioning
confidence: 99%